2017
DOI: 10.1186/s40249-017-0279-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-2015, why delay to seek healthcare? Perceptions and field experiences from TB healthcare providers in northern Malawi: a qualitative study

Abstract: BackgroundMalawi is a low-income country with high Tuberculosis (TB) burden. TB diagnosis delay and untimely initiation of treatment is still a major problem in Malawi which could increase the risk of tuberculosis transmission in the communities. This study investigated factors related to the diagnostic delay of tuberculosis from TB healthcare providers in the northern region of Malawi.MethodsNine focus group discussions were conducted with 57 participants in total. The participants were healthcare cadres incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(13 reference statements)
4
11
1
Order By: Relevance
“…In Ethiopia, Temesgen et al [ 39 ] also showed that more than 80% of healthcare professionals were not trained on tuberculosis infection control. Moreover, a health care provider not specialized in TB [ 37 ] and healthcare workers’ poor attitude towards potential patients [ 40 ] were found to be among the most influential factors behind the health system’s delay. Thus, further research on level of attitude, experience, knowledge and practice of health care professionals, and providing TB related training of all health professionals is warranted in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, Temesgen et al [ 39 ] also showed that more than 80% of healthcare professionals were not trained on tuberculosis infection control. Moreover, a health care provider not specialized in TB [ 37 ] and healthcare workers’ poor attitude towards potential patients [ 40 ] were found to be among the most influential factors behind the health system’s delay. Thus, further research on level of attitude, experience, knowledge and practice of health care professionals, and providing TB related training of all health professionals is warranted in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…FGD-based qualitative data collection is taking place in three of the 61 DrOTS participating villages as well as with the NTP–DrOTS mobile health team. Villages for the running of FGDs are selected based on1 participation in the DrOTS project for at least 3 months2; accessibility for the qualitative research team, meaning within a day’s hike from the closest vehicle-accessible town3 and willingness to host the DrOTS perception team. Collecting data in three villages enables comparison of reported perceptions and acceptability of new technologies across villages, the possibility for diversity in perceptions to be captured.…”
Section: Methods and Analysismentioning
confidence: 99%
“…One issue that requires managing in such a study is the risk of social stigma for participants. TB and association with TB are stigmatised in contexts around the world, and well documented in sub-Saharan Africa (eg,3 4 23–25 While there is no evidence of TB stigma in the Malagasy context of our research, we are adopting strategies to mitigate the risk of TB-related stigma developing for participants in our TB-focused study. In our initial meeting with CHWs in each village, we are stressing our interest in speaking with DrOTS-enrolled patients (TB active) but also our commitment to keeping the TB-active status of these patients private.…”
Section: Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Asia have reported stigma and limited knowledge among health practitioners as obstacles in the uptake of preventive, diagnostic and treatment services among HBV patients (4,23). Delayed health seeking behaviour has been widely reported in tuberculosis and is a result of several factors such as lack of symptoms, low patient knowledge, practising self-medication, and the use of traditional healing methods (24)(25)(26). In our study, the asymptomatic nature of HBV, poverty and lack of knowledge (including among healthcare workers) were challenges in accessing timely and appropriate healthcare (27).…”
Section: Stigmamentioning
confidence: 99%